Systematization, Description, and Territory of the Middle Cerebral Artery in Brain Surface of the Turtle (Trachemys scripta elegans) - Voll, Juliana; Campos, Rui (Acta Scientiae Veterinariae, 2016)
Background: Trachemys scripta elegans, in Brazil, has been considered an exotic and invasive turtle; it competes with autochthon species for habitat and food, threatening biodiversity. These animals have been exported to Brazil as pets; however, despite of the commercial interest in the last years, there are only few reports about the turtle central nervous system vascularization. Therefore, this study had the objective to describe and systematize the middle cerebral artery at the brain surface of the turtle (Trachemys scripta elegans), determining a standard model of irrigation and the main ramifications and territory, in this species. Materials, Methods & Results: Thirty turtles received pre-anesthetic medication composed of ketamine (80 mg/kg) and midazolam (2 mg/kg) followed by euthanasia with a sodium thiopental (100 mg/kg) overdose. The aortic arches were cannulated through the single ventricle, the cranial cava veins were incised and the vascular system washed with saline solution and heparin, and then filled with latex. Pieces remained immersed in running water and a bone window was opened in the cranial vault. Samples were fixed with formaldehyde and each brain with a spinal cord segment was removed from the cranial vault, the duramater was removed and the arteries dissected. Results were recorded and it was observed that the middle cerebral artery, collateral branch of the rostral branch of the internal carotid artery, varied between one to three components. These vessels anastomosed, originating a net that was projected from the base of the brain dorsorostralwards, reaching the convex surface of the olfactory bulb. Their lateral ramifications formed the convex hemispheric arteries, which ascended to the convex surface of the cerebral hemisphere and reached, caudally, the proximities of the caudal pole, anastomosing with the occipital hemispheric branches of the caudal cerebral artery and, dorsally, anastomosed with the caudal medial hemispheric branches of the caudal inter-hemispheric artery. Rostrally, its terminal branches, dorsal and ventral, formed a vascular ring around the coronal sulcus, which separated the cerebral hemisphere from the sessile olfactory bulb together with the rostral medial hemispheric branches of the rostral inter-hemispheric artery, branch of the rostral cerebral artery. The arteries of the olfactory bulb were originated from this ring. The middle cerebral artery in 63.4% of the samples to the right and in 56.7% to the left was double. But in 33.3% to the right and 20% to the left was triple, whereas in 3.3% to the right and in 23.3% to the left was a single vessel. Discussion: Authors reported that the middle cerebral artery, in reptiles, was originated as a single trunk, which subdivided into several arteries or was formed from several short trunks that ramified towards the convex surface of the cerebral hemisphere. In a study about turtles, the middle cerebral artery presented single origin and was emitted from the rostral branch of the internal carotid artery, emitting secondary branches that irrigated a portion of the dorsolateral surface of the cerebral hemispheres. In alligators, the rostral branch of the internal carotid artery originated a large middle cerebral artery, which emitted secondary branches towards the lateral surface of the cerebral hemisphere, continuing as rostral cerebral artery. In Cayman, the middle cerebral artery consisted of a formation of a net originated from one to five vessels, which was projected in sequence as collateral branches of the rostral branch of the internal carotid artery. This pattern of the middle cerebral artery was also observed in Trachemys, however, the net formation of the middle cerebral artery was after the emission of one to three vessels.